(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article provides a comparative analysis of the performance of historical epics in the repertoire of bakhshis of Uzbek folk epic schools, the peculiarities of the epics, the plot and motives, the epic mastery of bakhshis in the transformation of the historical image into a traditional type. The continuation of the poetic expression of historical reality and the image of individuals in the teacher-student tradition, the role of epic mastery and performance in the performance of epic schools and students are analyzed from a comparative typological point of view. Theoretical substantiation of the fact that live oral performances are an important factor in the continuation and preservation of generations is shown by the analysis of the epics "Shaibanikhan" and "Aychinar" written from the repertoire of the Polkan shair and Kadyr Bakhshi. The role of the epic tradition in the popularity of historical figures such as Shaibanikhan and Babur, who played an important role in the socio-cultural development of the people, the scientific theoretical conclusions about the factors of strengthening individual creative methods as a result of the influence of bakhshi literacy on epic memory and knowledge. The image of the historical figure and its ideological and literary features are studied in the epic.